An Unexpected Lymphoma: A Rare Case of Primary Gastric Burkitt's Lymphoma - Jonathan London MD; Sabrina Bulancea MD; Sharnjyot Wander MD; Shirley Ponnaiya DO; Leilah Tisheh MD; Sanjeev Jain MD; Prakash Viswanathan MD; Zubin Tharayil MD (SAGE Publishing, 2024)
Primary gastric Burkitt's lymphoma is an aggressive non-Hodgkin's lymphoma that has been rarely reported in the literature. The majority of primary gastric lymphomas are diffuse large B-cell lymphomas and mucosa-associated lymphoid tissue (MALT) lymphomas. Patients with primary gastric Burkitt's lymphoma can present with abdominal pain, hematemesis, melena, perforation, and obstruction. Diagnosis is made with a combination of clinical, radiological, and pathological findings. Treatment data are limited due to the limited cases reported. We present a case of a 47-year-old female who presented with diffuse abdominal pain, melena, and coffee-ground emesis that was diagnosed with primary gastric Burkitt's lymphoma following biopsies taken from a gastric ulcerated mass found on upper endoscopy.